Yolande Snaith Theatredance 2004 Review - Gilbert, Jenny (Dance Books Ltd., Alton,Hampshire (UK), 2004)
PALABRAS CLAVE: Yolande Snaith, Alice in Wonderland, Jardin Blanc.
Dentro del apartado "Dance Now. 2004 Reviews".